Implementation Flipped Classroom Based Video for Improving Interest Learning of Physics - Neneng Hadriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2021)
This study aims to increase students' interest in learning in the application of the flipped classroom learning model with video media, and the instruments used are pre-test and post-test questionnaires and observation sheets for observers. The analysis was carried out by checking the completeness of the survey, classifying the answers by giving scores and obtaining the Normalized Gain test results (N-Gain). This research was conducted at SMP IT ABU BAKAR FULLDAY SCHOOL class VII, with the research method Pre-Experimental designs with the form One-Gup Pretest-Posttest Design. Based on the results of research that has been carried out using the video-based flipped classroom model to increase student learning interest, the results obtained are 35% which is classified as moderate, seen from the normalized Gain criteria, if there are results 30 ≤ N-Gain ≤ 70, then it is in the medium category. Flipped classroom;physics learning, learning video, learning interest